M6A RNA Degradation Products Are Catabolized by an Evolutionarily Conserved N6-Methyl-AMP Deaminase in Plant and Mammalian Cells. Issue 7 (8th June 2018) - Chen, Mingjia; Urs, Mounashree J.; Sánchez-González, Ismael; Olayioye, Monilola A.; Herde, Marco; Witte, Claus-Peter
Abstract : A multilayer molecular protection system functioning in Arabidopsis and human cells suppresses the formation of N 6 -methyl-ATP, possibly to prevent random insertion of N 6 -methylated adenine into RNA. Abstract: N 6 -methylated adenine (m 6 A) is the most frequent posttranscriptional modification in eukaryotic mRNA. Turnover of RNA generates N 6 -methylated AMP (N 6 -mAMP), which has an unclear metabolic fate. We show that Arabidopsis thaliana and human cells require an N 6 -mAMP deaminase (ADAL, renamed MAPDA) to catabolize N 6 -mAMP to inosine monophosphate in vivo by hydrolytically removing the aminomethyl group. A phylogenetic, structural, and biochemical analysis revealed that many fungi partially or fully lack MAPDA, which coincides with a minor role of N 6 A-RNA methylation in these organisms. MAPDA likely protects RNA from m 6 A misincorporation. This is required because eukaryotic RNA polymerase can use N 6 -mATP as a substrate. Upon abrogation of MAPDA, root growth is slightly reduced, and the N 6 -methyladenosine, N 6 -mAMP, and N 6 -mATP concentrations are increased in Arabidopsis. Although this will potentially lead to m 6 A misincorporation into RNA, we show that the frequency is too low to be reliably detected in vivo. Since N 6 -mAMP was severalfold more abundant than N 6 -mATP in MAPDA mutants, we speculate that additional molecular filters suppress the generation of N 6 -mATP. Enzyme kinetic data indicate that adenylate kinases represent such filters being highly selective for AMP versus N 6 -mAMP phosphorylation. We conclude that a multilayer molecular protection system is in place preventing N 6 -mAMP accumulation and salvage.